Beyond "progressivism" a new "global paradigm" in public management. - Hood, Christopher (1996)
"This paper examines Osborne and Gaebler's well-known claim that a new "global paradigm" is emerging in public administration in the nineties. There has been a trend away from the doctrines of progressive public administration" in several countries, though it is less certain that the move is truly universal. Yet this paper argues that establishing the partial retreat of progressivism does not necessarily demonstrate that any single new style of public administration will "inevitably" be adopted worldwide to replace progressivism, or even that progressivism will everywhere disappear. Accordingly, public administration in the nineties may be facing a plural future, as services and reform emphases shift among these styles, rather than any single "new paradigm"
Keywords: Public administration - United States; Public administration